Imitation perfection: A simple rule to prevent discrimination in procurement - Helene Mass; Nicolas Fugger; Vitali Gretschko; Achim Wambach (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Procurement regulation aimed at curbing discrimination requires equal treatment of sellers. However, Deb and Pai (2017) show that such regulation imposes virtually no restrictions on the ability to discriminate. We propose a simple rule - imitation perfection - that restricts discrimination significantly. It ensures that in every equilibrium bidders with the same value distribution and the same valuation earn the same expected surplus. If all bidders are homogeneous, revenue and social surplus optimal auctions which are consistent with imitation perfection exist. For heterogeneous bidders however, it is incompatible with revenue and social surplus optimization. Thus, a trade-off between non-discrimination and optimality exists.
Keywords: D44; D73; D82; L13; 330; discrimination; symmetric auctions; procurement regulation